Teaching systematic synthetic phonics and early English - Glazzard, Jonathan; Stokoe, Jane (Critical teaching (Critical Publishing), 2017)
This is an essential guide to teaching primary English, with a focus on systematic synthetic phonics. The new edition has been fully revised and updated to reflect the structure, content and requirements of the national curriculum, and to include the latest policy context.